Tuning superior hydrophobic performance of Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC) via polydimethylsiloxane-based bulk modification - Yi-Xin Zhang; Ying-Hao Gao; Rui Lin; Wei Hou; Guo-Wei Yan; Jirong Lan; Ling-Yu Xu; Bo-Tao Huang (Materials & Design)
Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC) are renowned for their fine crack patterns during their service life. However, these cementitious composites inherently possess hydrophilic properties. Combined with multiple microcracks, moisture transmission would be further promoted, weakening the long-term durability of ECC. This study presented an innovative approach by introducing hydroxyl-terminated polydimethylsiloxane (PDMS) modification to transform the hydrophilic nature of specifically designed ECC into superior hydrophobic performance. Through this modification, a small quantity of PDMS was incorporated into the composite, resulting in a remarkable water contact angle exceeding 134.03°, with a 97.9% reduction of water absorption. A comprehensive evaluation of the impact of PDMS on wetting behavior, hydration degree, and mechanical properties of ECC was conducted. Micromechanical analysis and microscopic tests revealed that while PDMS reduced the hydration degree of the cementitious matrix, the chemical bonding within the interfacial transition zone (ITZ) between the fibers and matrix was strengthened, and an average tensile strain capacity of over 4% was preserved for ECC. These findings demonstrated the significant potential of PDMS-modified ECC for enhanced durability in infrastructure applications, particularly in moisture-rich or marine environments.